Portal thrombosis in antiphospholipid syndrome: Case report: Trombosis portal en Síndrome antifosfolipídico: Reporte de caso - Pelaes Cruz, Elkin J. (2022)
Antiphospholipid syndrome (APS) is a systemic autoimmune disorder characterized by arterial, venous, or small vessel thrombosis and recurrent early pregnancy loss, fetal loss, or pregnancy morbidity in the context of persistent antiphospholipid antibodies. Characterized by the development of multiple thrombotic manifestations, simultaneously or within a short period of time; being portal vein thrombosis (DVT) a rare and serious clinical manifestation and a predictor of poor prognosis.The case of an elderly patient with abdominal pain and portal vein thrombosis associated with APS with antithrombotic treatment and analgesics of favorable evolution is presented.